An Analysis of Oral Corrective Feedback Applied by the English Teachers in the EFL Classroom - Deza Aulia Sari; Usman Kasim; Diana Achmad (Research in English and Education Journal, 2022)
Oral corrective feedback is the teacher’s response and strategy toward students’ oral errors in the classroom especially in learning English as the target language. The study was aimed at finding out the types of oral corrective feedback dominantly used by the teachers at SMA Labschool USK Banda Aceh and their perceptions about oral corrective feedback. This research belongs to descriptive qualitative research using interview guide adopted from Fungula (2013) as the instrument of the research. To obtain the data, the researcher used interview dan recorded the data using smartphone. The findings show that there are four types of oral corrective feedback appeared as the types dominantly used by the teachers namely; recast, metalinguistic feedback, elicitation, and repetition. Furthermore, the teachers have positive opinions about oral corrective feedback. The teachers also explained the way they applied oral corrective feedback and the appropriate timing in providing the feedback. In their opinions, they believed they should adaptable and flexible in using various types of oral corrective feedback in order to obtain the best outcome on learners’ speaking skill in English. Regarding to the result, the researcher suggests the English teachers enhance their awareness about the advantages of different types of oral corrective feedback. In addition, future studies is needed on the learners’ uptake and their perceptions toward oral corrective feedback, as well as students’ preferences regarding explicit or implicit feedbacks.